Haley and the Blowfish - Mark D. West (Washington University Global Studies Law Review, 2009)
In this Article, I want to explore these two insights of Haley’s in an off-the-beaten-path subject of regulation: blowfish. (That I am able to get so far off the beaten path is a luxury I owe to Haley, who, with a few others, created the path in the first place.) I ask two questions. First, why have blowfish poisoning rates fallen over time? Second, why do so few blowfish poisoning cases go to court?
Keywords: Adversary system (Law) -- Japan; Adversary system (Law) -- United States; Puffers (Fish); Food supply -- Safety measures; Consensus (Social sciences); Administrative law; Comparative law; John Owen Haley; Takeyoshi Kawashima